Effects of 21-kHz intermediate frequency magnetic fields on blood properties and immune systems of juvenile rats. (December 2014) - Ushiyama, Akira; Ohtani, Shin; Suzuki, Yukihisa; Wada, Keiji; Kunugita, Naoki; Ohkubo, Chiyoji
Abstract Purpose: Due to a lack of science-based evidence, we explored the effects of exposure to intermediate frequency magnetic fields (IF-MF) on experimental animals. We assessed several immunological parameters to determine the effect of exposure of the whole body to IF-MF. Materials and methods: Male Sprague-Dawley rats (4–5 weeks old) were divided into three groups: Cage-control, sham, and 3.8-mT (rms) exposure groups. The animals were exposed to IF-MF at 21 kHz under fixed conditions in an acrylic holder. Exposure was performed for 1 h/day for 14 consecutive days. On the 15th day following the exposure, biochemical and hematological parameters in blood were analyzed. The effects of the exposure on immunological functions such as the cytotoxic activity of lymphocytes, chemotactic and phagocytic activity of granulocytes, and T (cluster of differentiation 4 [CD4] and cluster of differentiation 8 [CD8])-cell frequency were also examined. Results: Hematological parameters were not affected by IF-MF exposure. Other immune functions such as the cytotoxic activity and phagocytic activity were not affected. Populations of T cells after exposure also did not show any significant differences. In blood biochemistry, there was significant difference in inorganic phosphorus level between sham and exposure group. However, this will not induce any pathophysiological status, because they were still within physiological range. Overall, no significant effect by exposure of IF-MF was observed under our experimental conditions. Conclusions: Our results suggest that exposure to 21-kHz sinusoidal IF-MF at 3.8 mT for 1 h/day for 14 days did not affect immune function in juvenile rats.